Medical Emergency and Public Health Response in Disaster Settings: A Case Series of Pidie Jaya, Lombok and Palu Earthquakes - Safrizal Rahman; Muhammad Bayu Zohari Hutagalung (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Indonesia is one of the most disaster-prone countries, often regarded as a “world disaster laboratory.” Natural disasters cause destruction and human suffering, especially in low- and middle-income countries Objective: This paper presents the overview of a medical emergency and public health response towards several recent earthquakes in Pidie Jaya, Lombok, and Palu of Indonesia. Case Series: The authors examine the appropriateness and effectiveness of the organized disaster response of the Pidie Jaya, Lombok, and Palu earthquakes in medical emergency response. Pidie Jaya Earthquake: A 6.4 magnitude earthquake struck off Pidie Jaya Regency, province of Aceh in Sumatra Island, Indonesia, resulting in 104 people died and others 395 injured. Lombok Earthquake: A series of moderate and strong earthquakes have rocked cities and regencies in Lombok Island, West Nusa Tenggara (NTB) causing 436 people died, 783 people with severe injury and 570 people with a mild injury. Palu Earthquake: The 7.7 magnitude earthquake hit Donggala district and also affected Palu city and Parigi Mountong regency causing 2657 people died, 4471 people with severe injury and 87,835 people with a mild injury. Important Findings: Though Indonesia has made outstanding progress in disaster management, the country still has many challenges and problems to overcome. The integration of data and information about health needs the progress of relief work, and about various other problems related to health is one of the most urgent and vital for better improving the medical emergency response and public health-related support in disaster settings.